New tricks. Season 11 [videorecording (DVD)]. - Hay, Andy, 1954-; Outhwaite, Tamzin, 1970-; Waterman, Dennis, 1948 February 24-; Lawson, Denis (Acorn, 2015)
The veteran detectives of the Unsolved Crime and Open Case Squad (UCOS) continue to solve cold cases, now with a new boss, DCI Sasha Miller.